Monitoring Application Complaints of Internet Service Provider Interference Using Waterfall Method (Case Studies: Indihome Pasar Baru Tangerang) - H, I Made Willy Prasetya; Husufa, Nurullah (Journal of Information Systems and Informatics, 2023)
The impact of information systems and technology on various industries, including internet services like Indihome, is substantial. However, providing seamless access to Indihome internet services remains a challenge for PT Telkom Akses, particularly at their Pasar Baru Tangerang branch. One of the issues faced by staff members when handling complaints from internet service users is the lack of integration between the manual data management system and Telegram, which could automate operations and streamline the process of distributing trouble tickets. The current process for distributing trouble tickets is also inefficient, relying on manual copying and pasting. To address these issues, the application was developed using the PHP programming language, Codeigniter Framework, and MySQL, and the Waterfall method was employed in the design process. The application includes features such as Add Data Datin, Add Data Non Datin, Close Data Datin, Close Data Non Datin, and Telegram bots to facilitate complaint monitoring and ticket distribution.
Keywords: Web Monitoring Complaint; Internet Service Provider; Interference Ticket; Telegram Bot